Novel cookie formulation with defatted sesame flour: Evaluation of its technological and sensory properties. Changes in phenolic profile, antioxidant activity, and gut microbiota after simulated gastrointestinal digestion. (30th September 2022) - Lucini Mas, Agustin; Brigante, Federico I.; Salvucci, Emiliano; Ribotta, Pablo; Martinez, Marcela L.; Wunderlin, Daniel A.; Baroni, María V.
Graphical abstract: Highlights: Defatted sesame flour supplementation did not modify the cookies' overall technological quality. Cookies with defatted sesame flour were preferred by consumers over the control formulation. Supplemented cookies showed better antioxidant capacity than control before and after digestion. Only 19% of polyphenols in supplemented cookies would be potentially absorbed after digestion. Sesame defatted flour showed beneficial effects on the gut microbiota. Abstract: Defatted sesame flour (DSF), a coproduct of the sesame oil extraction process, is often discarded despite having high polyphenol content. The aim of this study was to improve the antioxidant properties of cookies with increasing amounts of DSF (5, 10, and 20%) and study its impact on processing and gastrointestinal digestion. Besides, we evaluated the effect of this incorporation on the technological and sensory properties of cookies. The formulation with 10% (SFC10) showed technological quality similar to control, and was the most accepted by consumers. After baking, 13 out of 25 polyphenols from DSF were observed, and only 19% of the initial SFC10 polyphenols would be potentially absorbed after digestion. Besides, the addition of DSF benefits the microbiota composition after colonic fermentation. In conclusion, supplementation with 10% of DSF in cookies improves sensorial acceptance and antioxidant properties, without affecting the technological ones.